2021
DOI: 10.1016/j.isci.2021.102267
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive label-free imaging of brain samples using FxClear-based tissue clearing technique

Abstract: Summary Optical clearing has emerged as a powerful tool for volume imaging. Although volume imaging with immunostaining have been successful in many protocols, yet obtaining homogeneously stained thick samples remains challenging. Here, we propose a method for label-free imaging of brain slices by enhancing the regional heterogeneity of the optical properties using the tissue clearing principle. We used FxClear, a method for delipidation of brain tissue, to retain a larger proportion of lipids at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previously, we demonstrated that label-free imaging with selective-plane illumination microscopy (SPIM) microscopy is applicable to whole-organ imaging in combination with a tissue-clearing procedure 24 . The source of label-free signals is multiple organic materials including lipids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that label-free imaging with selective-plane illumination microscopy (SPIM) microscopy is applicable to whole-organ imaging in combination with a tissue-clearing procedure 24 . The source of label-free signals is multiple organic materials including lipids.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of these processes is strongly associated with hydrophobicity/hydrophilicity of biological specimens. For instance, tissue transparency is differentially affected by lipid content and the average RI value 17 , 24 27 . In lipid-rich organs, de-lipidation is essential to achieve a substantial degree of transparency.…”
Section: Introductionmentioning
confidence: 99%